基于语块理论的新加坡小学口语教学设计研究 - Yan Dong (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2026)
Against the background of current Chinese language teaching in Singapore primary schools, this study adopts chunk theory as its theoretical framework to examine the effectiveness of chunk-based instruction in improving students’ oral proficiency. A total of 103 students with comparable Chinese language proficiency from five Primary 4 to Primary 6 classes participated in the study. A cross-school teacher team conducted a semester-long teaching intervention. Data was collected through audio and video recordings, classroom observations, and student assignments. The study identified practical procedures for chunk extraction and instruction and provided preliminary evidence that such intervention enhances students’ chunk awareness, as well as their oral fluency and accuracy. The findings indicate that integrating chunk theory into the existing curriculum, supported by digital teaching methods and diversified interventions, can significantly stimulate primary school students’ motivation for oral input and output, and improve the retention and productive use of chunks. This approach is particularly beneficial for improving the oral performance of L2 learners with relatively low levels of Chinese proficiency.